Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can-SOLVE CKD): Form and Function. Issue 1 (16th January 2018) - Levin, Adeera; Adams, Evan; Barrett, Brendan J.; Beanlands, Heather; Burns, Kevin D.; Chiu, Helen Hoi-Lun; Chong, Kate; Dart, Allison; Ferera, Jack; Fernandez, Nicolas; Fowler, Elisabeth; Garg, Amit X.; et al.
Purpose of review: This article serves to describe the Can-SOLVE CKD network, a program of research projects and infrastructure that has excited patients and given them hope that we can truly transform the care they receive. Issue: Chronic kidney disease (CKD) is a complex disorder that affects more than 4 million Canadians and costs the Canadian health care system more than 40 billion per year. The evidence base for guiding care in CKD is small, and even in areas where evidence exists, uptake of evidence into clinical practice has been slow. Compounding these complexities are the variations in outcomes for patients with CKD and difficulties predicting who is most likely to develop complications over time. Clearly these gaps in our knowledge and understanding of CKD need to be filled, but the current state of CKD research is not where it needs to be. A culture of clinical trials and inquiry into the disease is lacking, and much of the existing evidence base addresses the concerns of the researchers but not necessarily those of the patients. Program overview: The Canadian Institutes of Health Research (CIHR) has launched the national Strategy for Patient-Oriented Research (SPOR), a coalition of federal, provincial, and territorial partners dedicated to integrating research into care. Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can-SOLVE CKD) is one of five pan-Canadian chronic kidney disease networks supported through the SPOR. The vision of Can-SOLVE CKD is that by 2020 every Canadian with or at high risk for CKD will receive the best recommended care, experience optimal outcomes, and have the opportunity to participate in studies with novel therapies, regardless of age, sex, gender, location, or ethnicity. Program objective: The overarching objective of Can-SOLVE CKD is to accelerate the translation of knowledge about CKD into clinical research and practice. By focusing on the patient's voice and implementing relevant findings in real time, Can-SOLVE CKD will transform the care that CKD patients receive, and will improve kidney health for future generations.